Terusir - Hamka, 1908-1981. (Djakarta : Hikmat, 1963)
It relates the story of a faithful wife slandered by her mother-in-law and consequently driven away by her husband. The wife comes from a poor family while the husband is from a rich and a noble background.
Keywords: Indonesian fiction